Pengembangan E-Book Berbantuan Website Kodular Berbasis Project Based Learning Terhadap Literasi Sains Kelas X Materi Virus di SMA Santun Untan Pontianak - Meigito, Moses; Nawawi, Nawawi; Sari, Mustika (Universitas PGRI Semarang, 2024)
The 21st century is an era where advances in technology, communication and informatics continue to develop following the times. The developments that occur in the 21st century affect various aspects of education. Where the choice of learning media is very influential in learning so that by utilizing technology that is attractive, picturesque, and easy to carry and anytime one of them is E-book media. The purpose of this study is to determine the validity, practicality, and effectiveness of E-books on Project-Based Learning-based virus materials on science literacy in class X of SMA Santun Untan Pontianak. The research method used is Research and Development (RD) with the ADDIE model which consists of five stages, namely analyze, design, development, implementation, and evaluation. The instruments used include validation sheets, response questionnaires, and posttest pretests. The research sample was taken using a saturated sampling technique, namely with the population of class X of SMA Santun Untan Pontianak. The data analysis techniques used are in the form of validity, practicality, and effectiveness tests. The results of the study showed that the average assessment from material and media experts reached 90.78% with very valid criteria. The average student response questionnaire was 93.12% with very practical criteria. Meanwhile, the average N-Gain from the pretest and posttest results reached 0.78 with high criteria. Based on these results, it can be concluded that e-books assisted by Project Based Learning-based Kodular Websites are very valid, very practical, and effective for students to use as learning support.